Recurrent mutations at codon 625 of the splicing factor SF3B1 in uveal melanoma - Harbour, J. William (2013)
Uveal melanoma is the most common primary cancer of the eye and often results in fatal metastasis. Here, we describe mutations occurring exclusively at arginine-625 in splicing factor 3B subunit 1 (SF3B1) in low-grade uveal melanomas with good prognosis. Thus, uveal melanoma is among a small group of cancers associated with SF3B1 mutation, and these mutations denote a distinct molecular subset of uveal melanomas.